Integrasi Teknologi Artificial Intelligence Dalam Sistem Akuntansi Modern - Muh. Fathir Maulid Yusuf; Ika Maya Sari; Ahmad Hamid; Ilham Akbar Garusu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Artificial Intelligence (AI) has transformed the landscape of business and industries as a whole, including the field of accounting. The implementation of AI systems in accounting has brought significant changes, accelerating processes, enhancing efficiency, improving reporting accuracy, boosting analytical capabilities within accounting departments, and providing deep insights for accounting professionals. The objective is to explore the extent to which the integration of AI technology changes how organizations manage and analyze financial data, as well as providing insights for better decision-making. This research method employs a qualitative descriptive approach. Previous research literature is analyzed and explored. The research findings indicate that the integration of AI technology into accounting systems can yield operational efficiency by automating routine tasks, enhancing financial reporting accuracy through in-depth data analysis, and strengthening predictive capabilities in decision-making. The conclusion of this research is that the integration of AI technology into accounting systems has the potential to bring about transformative changes in how organizations manage finances and make decisions.